Intercropping with potato-onion alters arbuscular mycorrhizal fungi spore-associated bacterial communities of tomato rhizosphere - Zhou, Liyan; Pan, Xinjie; Zhang, Zihan; Zhang, Ying; Wu, Fengzhi; Gao, Danmei (Frontiers in Microbiology, 2025)
Intercropping systems optimize soil ecological functions, modulate microbial diversity, and enhance crop productivity. Arbuscular mycorrhizal fungi (AMF) are key soil symbionts that facilitate nutrient acquisition and enhance stress resilience in host plants. Notably, the AMF spore-associated bacterial communities that play a key role in maintaining AMF spore viability and supporting AMF function remain understudied in intercropping systems. This knowledge gap limits our ability to optimize intercropping's ecological benefits (e.g., enhanced soil fertility, reduced reliance on chemical fertilizers) by leveraging plant-AMF-bacteria synergies, which are critical for sustainable agriculture. This study compared the effects of tomato (Solanum lycopersicum L.) monocropping vs. tomato/potato-onion (Allium cepa L. var. aggregatum G. Don) intercropping on the composition and diversity of AMF spore-associated bacterial communities in the tomato rhizosphere under controlled greenhouse conditions, using Illumina MiSeq sequencing of the 16S rRNA gene V3–V4 region. The results demonstrated that compared with tomato monocropping, tomato/potato-onion intercropping significantly increased the alpha diversity (Shannon and Chao1 indices) of AMF spore-associated bacterial communities in the tomato rhizosphere (Student's t-test, P < 0.05) and markedly altered their taxonomic composition. Taxa significantly enriched under the intercropping system included the phyla Actinobacteriota and Cyanobacteria, the classes Alphaproteobacteria and Actinobacteria (a class of phylum Actinobacteriota), and the genera Janthinobacterium, Rhodococcus, Paenarthrobacter, and Streptomyces. Differential analysis identified 156 significantly shifted OTUs, with 137 enriched (predominantly Proteobacteria/Actinobacteria) and 19 depleted (mostly Bacteroidetes/Proteobacteria) in intercropping. These findings demonstrate that tomato/potato-onion intercropping reshapes AMF spore-associated microbiomes, selectively enriching microbial taxa with putative functions in nutrient cycling and plant growth promotion.